ESP NEEDS ANALYSIS FOR SYLLABUS DESIGN IN COMMUNICATION SCIENCE STUDY PROGRAM: A LEARNING-CENTRED APPROACH - Meiristiani, Noeris; Rosdiana, Ihda (Jurnal Bahasa Inggris, 2017)
English subject learnt by students of Communication Science Study Program is, of course, different from English for other study programs. English learning has to be in line with the needs of Communication Science students that are considered from the target needs (necessities, lacks, and wants) and learning needs. This research focuses on the needs analysis by applying learning-centred approach and syllabus outline that will be constructed based on the result of the needs analysis. It is a qualitative research that uses questionnaire and interview as the instruments. There are 30 students as the respondents and 2 lecturers in Communication Science Study Program as the interviewees. The collected data were reduced, displayed, and concluded. The syllabus outline resulted from the need analysis emphasized on speaking skill as expected by the students even though they still have more problems in writing and pronunciation. Therefore, the materials that will be designed based on the students? need have to pay attention to the activities for speaking performance. In addition, it also has to address the students? lack by assigning tasks on writing and pronunciation exercises. The learning centered approach allows the syllabus designers to adjust the learning activities that are favorable for the students. Thus, the syllabus outline can be flexibly used to adjust students? learning needs.